Revisión Bibliográfica Del Plasma Rico En Plaquetas Para La Reparación Celular De Las Opacidades Corneales (2021)
An exhaustive bibliographic review was carried out in order to determine the effect of platelet-rich plasma (PRP) in the cellular repair of corneal opacities. Currently, this alteration represents a therapeutic challenge for the restoration of transparency and conventional treatments do not always allow a rapid and complete resolution of the condition, which is why the need arises to search for new and efficient therapeutic alternatives. Methodology: bibliographic review in databases: PubMed, Medline, Scopus, Scielo, Acces Medicine, Mc Graw-Hill, using a snowball search strategy from 2000 to 2020. The variables analyzed were recovery time, application rates and adverse effects. The articles were classified and analyzed using the CASPe tool. Results: an analysis was performed by different groups of affectation (ulcers, unspecified wound healing (NE), degenerations, erosions). Conclusions: it is determined that PRP is an effective and safe treatment for cellular repair of corneal opacities.